2020
DOI: 10.3390/ijerph17093185
|View full text |Cite
|
Sign up to set email alerts
|

Flu Vaccination Attitudes, Behaviours, and Knowledge among Health Workers

Abstract: The aim of this work is to evaluate the attitudes, behaviours, and knowledge of health workers employed at an Italian University Hospital on the topic of vaccinations and in regard to flu vaccination. To this end, the study provided for the articulation of a computerised questionnaire on the digital platform EUSurvey which was administered online via e-mail to a sample of 457 health workers, in the period between November 2018 and March 2019. The data were subjected to descriptive and inferential statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 39 publications
(42 reference statements)
3
63
2
3
Order By: Relevance
“…A person’s decision-making process regarding health choices is, indeed, strongly influenced by what they read online, especially in relation to health issues such as vaccination [ 25 , 26 , 27 ]. According to the World Health Organization (WHO), pandemic-related interruptions in vaccination services and conflicting information on the Internet about SARS-CoV-2 vaccines have further affected vaccination compliance [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…A person’s decision-making process regarding health choices is, indeed, strongly influenced by what they read online, especially in relation to health issues such as vaccination [ 25 , 26 , 27 ]. According to the World Health Organization (WHO), pandemic-related interruptions in vaccination services and conflicting information on the Internet about SARS-CoV-2 vaccines have further affected vaccination compliance [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 In our study, majority of the study population reported that they had known the risk groups for influenza vaccination. Although each risk category was not specified in this study, subjects with diseases of the hematopoietic organs or chronic circulatory, respiratory, or renal conditions, cohabitants of at-risk subjects, and people over 65 years of age were the mostly reported risk groups by the HCW responders in the study by Arghittu et al 6 While interpreting the results of this study, some limitations should be considered. This study was conducted in our tertiary care hospital in Turkey.…”
Section: Influenza Vaccinementioning
confidence: 88%
“…Vaccination of HCWs has been recommended by CDC since 1981. 3 Vaccination of doctors and nurses and reasons for barriers of nonvaccination have been widely investigated until now [4][5][6] However, vaccine candidate HCWs, including medical students and nurse trainees had insufficient knowledge, about flu and flu vaccination. In addition, Turkish caregivers are under-evaluated, too.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines Di Martino et al also considered the main reason for missing flu vaccination was the presumed uselessness of the vaccine [ 46 ]. In another research [ 47 ] it was observed that the anti-influenza vaccination coverage of HCWs in Italy is far below the minimum targets set. The authors consider the informative role of the occupational physicians as fundamental to increase the awareness of the potential of the flu vaccine.…”
Section: Infectious Diseases 1- Hand Washing; 2- Enterovirus; 3- Ostmentioning
confidence: 99%